Generating bicliques of a graph - Figueiredo, Celina; Dias, Vânia (Cadernos do IME - Série Informática, 2022)
This is an account of the collaboration and research with Jayme Luiz Szwarcfiter and Celina Miraglia Herrera de Figueiredo during the development of the thesis of Vânia Maria Felix Dias at COPPE, "Geração de Bicliques em Grafos", finished in 2004, and its two subsequent journal papers.